William Spencer correspondence - Spencer, William, clergyman
ALS written by Spencer to an unknown recipient expressing his religious views and his opposition to slavery.
Methodist clergyman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Methodist Church -- Clergy; Religion; Slavery; Clergy